Dean Mosman letter to Nicholas S. Halmi regarding winter bird sightings, February 10, 1979 - Mosman, Deanet al (1979)
Letter from Dean Mosman to Nicholas S. Halmi regarding winter bird sightings from Saylorville Lake, Saylorville Dam and a feeding station, February 10, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed